DYNAMICS AND LEVEL OF DEVELOPMENT OF THE TOURISM SECTOR IN THE REPUBLIC OF MACEDONIA IN CONDITIONS OF TRANSITION AND MARKET ECONOMY - Iliev, Dejan; Mijalov, Risto; Kitevski, Goran (Faculty of Economics, University of Banja Luka, 2014)
After the 1991 there’s a period of development of the Republic of Macedonia on the principles of market economy. It is a period of economic transition and structural reforms in all spheres of the economic system and creation of a new integrated market economic system. Tourism, as part of the economic system of the country is evolving in a market conditions, and vast majority of the tourism organizations and enterprises (hotel accommodations, restaurants and other catering and accommodation facilities) are restructured from social to private enterprises; new hotels and other accommodation facilities were built but in most, they are smaller and most of the family business character. It is a very complex and unstable period which brings new changes in the development of the tourism industry, which contributed to the changes in the social sphere (reduction of employment, reduction of the actual amount of salaries etc,...). Therefore, the main objective of this research is to present the dynamics and degree of development of the tourism industry in the country in terms of market economy and the problems and perspectives in the development.
Keywords: economy, tourist sector, tourist revenue, GDP, employment